Reelin Is Required for Maintenance of Granule Cell Lamination in the Healthy and Epileptic Hippocampus - Orcinha, Catarina; Kilias, Antje; Paschen, Enya; Follo, Marie; Haas, Carola A. (Frontiers in Molecular Neuroscience, 2021)
One characteristic feature of mesial temporal lobe epilepsy is granule cell dispersion (GCD), a pathological widening of the granule cell layer in the dentate gyrus. The loss of the extracellular matrix protein Reelin, an important positional cue for neurons, correlates with GCD formation in MTLE patients and in rodent epilepsy models. Here, we used organotypic hippocampal slice cultures (OHSC) from transgenic mice expressing enhanced green fluorescent protein (eGFP) in differentiated granule cells (GCs) to monitor GCD formation dynamically by live cell video microscopy and to investigate the role of Reelin in this process. We present evidence that following treatment with the glutamate receptor agonist kainate (KA), eGFP-positive GCs migrated mainly towards the hilar region. In the hilus, Reelin-producing neurons were rapidly lost following KA treatment as shown in a detailed time series. Addition of recombinant Reelin fragments to the medium effectively prevented the KA-triggered movement of eGFP-positive GCs. Placement of Reelin-coated beads into the hilus of KA-treated cultures stopped the migration of GCs in a distance-dependent manner. In addition, quantitative Western blot analysis revealed that KA treatment affects the Reelin signal transduction pathway by increasing intracellular adaptor protein Disabled-1 synthesis and reducing the phosphorylation of cofilin, a downstream target of the Reelin pathway. Both events were normalized by addition of recombinant Reelin fragments. Finally, following neutralization of Reelin in healthy OHSC by incubation with the function-blocking CR-50 Reelin antibody, GCs started to migrate without any direction preference. Together, our findings demonstrate that normotopic position of Reelin is essential for the maintenance of GC lamination in the dentate gyrus and that GCD is the result of a local Reelin deficiency.